Entity Framework Core in action - Smith, Jon P. (Manning Publications, 2021)
Entity Framework Core in Action, Second Edition is an in-depth guide to reading and writing databases with EF Core. Revised from the bestselling original edition, it's filled with over 100 diagrams, code snippets, and examples--including building and scaling your own bookselling web application. Learn from author Jon Smith's extensive experience working with EF Core in production, as you discover time-saving patterns and best practices for security, performance tuning, and unit testing. All of the book's code is available on GitHub. About the Technology Entity Framework radically simplifies data access in .NET applications. This easy-to-use object-relational mapper (ORM) lets you write database code in pure C#. It automatically maps classes to database tables and enables queries with standard LINQ commands. It even generates SQL, so you don't have to! About the Book Entity Framework Core in Action, Second Edition teaches you to write flawless database interactions for .NET applications. Following relevant examples from author Jon Smith's extensive experience, you'll progress quickly from EF basics to advanced techniques. In addition to the latest EF features, this book addresses performance, security, refactoring, and unit testing. This updated edition also contains new material on NoSQL databases. What's Inside Configuring EF to define every table and column Updating your schema as your app grows Integrating EF with existing C# application Writing and testing business logic for database access Applying a Domain-Driven Design to EF Core Getting the best performance out of EF Core About the Reader For .NET developers familiar with relational databases. About the Author Jon P. Smith is a freelance software developer and architect with a special focus on .NET and Azure. Quotes The most comprehensive reference for EF Core that does--or ever will--exist. - Stephen Byrne, Intel Corporation The definitive guide to EF Core. Filled with real world examples, it's the most practical way to enhance your EF Core skill set. - Paul Brown, Diversified Services Network I firmly believe anyone using EF Core will find something to up their game in this book. - Anne Epstein, Headspring Remains a go-to resource for me while working with Entity Framework. - Foster Haines, J2 Interactive.
Online resource; title from title details screen (O'Reilly, viewed August 29, 2023)
Keywords: Entity Framework (Software framework); Database design; Relational databases; Bases de données; Conception; Bases de données relationnelles; Audiobooks; Livres audio